2019
DOI: 10.1007/s10158-019-0229-7
|View full text |Cite
|
Sign up to set email alerts
|

The allelochemical tannic acid affects the locomotion and feeding behaviour of the pond snail, Lymnaea stagnalis, by inhibiting peripheral pathways

Abstract: (1) The effect of tannic acid (TA), a dominant component of plant allelochemicals, was investigated on the locomotion and feeding of the pond snail, Lymnaea stagnalis . The effect of TA on the neuronal background underlying feeding activity was also analysed. (2) TA affected the spontaneous locomotion and of juvenile snails in a concentration-dependent way. Low (10 μM) TA concentration resulted in an increased (sliding or swimming) activity compared to the control; meanwhile, high (100 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…However, the neuromodulator role of monoamines has been well confirmed in the regulation of snail locomotion (Pavlova, 2019). It is assumed that light information influences ciliary activity directly, either by directly influencing 5-HT receptors or by hitting the serotonergic regulatory pathway(s) via an afferent-efferent system that includes receptor cells on the foot's surface and central (pedal) serotonergic efferent elements (Vehovszky et al, 2019). More investigations are needed to establish the stress level that LED light offers to the aquatic environment, including snails.…”
Section: Discussionmentioning
confidence: 99%
“…However, the neuromodulator role of monoamines has been well confirmed in the regulation of snail locomotion (Pavlova, 2019). It is assumed that light information influences ciliary activity directly, either by directly influencing 5-HT receptors or by hitting the serotonergic regulatory pathway(s) via an afferent-efferent system that includes receptor cells on the foot's surface and central (pedal) serotonergic efferent elements (Vehovszky et al, 2019). More investigations are needed to establish the stress level that LED light offers to the aquatic environment, including snails.…”
Section: Discussionmentioning
confidence: 99%
“…These types of local networks including interaction between the sensory and efferent elements may ensure fast and definitive responses to different sensory stimuli. In a recent study on Lymnea , Vehovszky et al ( 2019 ) have demonstrated that following the application of the allelochemical tannic acid, both the afferent and efferent peripheral functions were affected. Feeding activity was reduced by blocking the sensory pathway and the locomotion activity was also inhibited, supposedly also through the sensory afferents.…”
Section: Discussionmentioning
confidence: 99%